Da'wah Approach In The Millennial Era - Saliudin Hasim (Jurnal Syntax Transformation, 2023)
Media must really be utilized in the millennial era. Nowadays almost everyone uses the internet in sending, searching and reading information. In addition, in interacting too, most of it is done through social media rather than communicating directly. Millennials have authority over themselves in using the media they access. The millennial generation is able to show distinctive patterns of diversity influenced by technology. The internet is used as a teacher and friend for the digital society. The digital generation is a new group that receives da'wah messages with contemporary concepts. Network communities that are active in commenting, criticizing and carrying out da'wah activities by sharing through the platform used. In approaching da'wah, the Prophet SAW taught us his people to deliver Islamic da'wah according to the language, terminology and perspective of the target of da'wah itself. It is a must for dai and daiyah to know the ins and outs of the terminology and communication model of the millennial generation to make it easier for him to convey da'wah messages.